No Drama: Key Elements to the Success of an HIV/STI-Prevention Mass-Media Campaign. (May 2014) - Pedrana, Alisa E.; Hellard, Margaret E.; Higgs, Peter; Asselin, Jason; Batrouney, Colin; Stoovè, Mark
We qualitatively examined gay men's reactions to the national "Drama Downunder" HIV/STI social marketing campaign targeting gay men in Australia to identify key campaign elements that underpinned the demonstrated effectiveness of the campaign. We present findings from six qualitative focus groups held with 49 participants as part of the evaluation of the sexual-health-promotion campaign over 2008–2009. Participants identified attention-grabbing images, a humorous approach, positive and simple tailored messaging, and the use of mainstream media as campaign features crucial in normalizing sexual health testing, driving campaign engagement, and ensuring high message exposure. Our results suggest that designers of future campaigns should strive to balance positive and negative campaign images and messages, and find new ways to engage men with sexual health topics, particularly younger gay men. We discuss the implications of our findings about campaign effectiveness for future health-promotion campaigns and message design.